The Influence of Interest and Benefits of Using Mobile Banking on the Financial Behavior of Generation Z at PT Bank Sumut Central Medan City - Kristiani Erlin Telaumbanua; Yeni Ariesa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was carried out in Medan City at PT Bank Sumut Central. The aim of this study was to ascertain the degree of PT Bank Sumut Medan City Center customers' interest in using mobile banking, as well as the advantages of doing so and their financial behavior with regard to Generation Z. The reason mobile banking is so simple to use is that generation Z can pick up the basics of using it quickly since the system is intuitive, clear, and uncomplicated. This study used a quantitative approach, processing data from 150 generation Z clients through the use of SPSS. The study's findings show that interest in using mobile banking (X1) did not have a significant effect, at least not in the partial sense (t test). favorable and noteworthy impact on the financial behavior of Generation Z (Y). This is evident from the significance value obtained (1.000 > 0.05) and the computed t value, which is less than the t table (0.000 < 1.986), indicating that Ha is rejected and Ho is accepted. The Benefits of Using Mobile Banking (X2) did not significantly and favorably affect Generation Z's financial behavior (Y), according to partial data (t test). This is evident from the significance value obtained (1.000 > 0.05) and the computed t value, which is less than the t table (0.000 < 1.986), indicating that Ha is rejected and Ho is accepted